A Compact High-Gain, High-Power, Ultrashort Pulse Signal Acquisition Device. (1st March 2023) - Fang, Jinyong; Zhai, Chang; Wu, Jiangniu; Zhang, Haoliang; Huang, Huijun; Li, Qiwei
Abstract : Ultrashort pulse (USP) signal with high peak power is also called ultrawideband signal, which has a broad application prospect in radar detection and electronic countermeasures and other fields. In this paper, an acquisition device is proposed to obtain the USP signal with ultrahigh compression efficiency (CE) and ultrahigh power compression gain (PCG). The long input pulse with a time length of μ s level can be compressed to a narrow pulse with a pulse width of 450 ps level (2.6–3.9 GHz) by using the proposed USP acquisition device. Under the condition without loss, the CE of the USP acquisition device can reach up to 98% according to the simulated results. In the simulation, if the material of the acquisition device is set to copper material, then the CE has some reduction due to conductor loss. In order to demonstrate the effectiveness of the proposed USP acquisition device, a USP acquisition device is established and measured. According to the measurement results, a measured PCG of 27 dB is achieved and the pulse width is approximately 460 ps. The peak power of the output USP signal reaches to 100 kW under the condition of input pulse with a power of 200 W.